THE TEACHER AS A SUBJECT OF THE PEDAGOGICAL PROCESS - Axmadjonova Oydinoy; No'monjonova Gulnoza (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract This  article  explores  the  essential  role  of  the  teacher  as  a  subject  of  the pedagogical  process.  It  examines  the  teacher’s  influence  not  only  as  a  source  of knowledge but also as a guide, motivator, and moral model for students. The article highlights  the  key  responsibilities,  professional  competencies,  and  human  qualities required for effective teaching. It also underlines the importance of teacher-student interaction,  self-reflection,  and  continuous  professional  development  in  shaping  an effective educational environment.